Human hematopoietic stem/progenitor cells display reactive oxygen species-dependent long-term hematopoietic defects after exposure to low doses of ionizing radiations - Elia Henry; Inès Souissi-Sahraoui; Margaux Deynoux; Andréas Lefèvre; Vilma Barroca; Anna Campalans; Véronique Ménard; Julien Calvo; Françoise Pflumio; Marie-Laure Arcangeli (Haematologica, 2020)
Hematopoietic stem cells are responsible for life-long blood cell production and are highly sensitive to exogenous stresses. The effects of low doses of ionizing radiations on radiosensitive tissues such as the hematopoietic tissue are still unknown despite their increasing use in medical imaging. Here, we study the consequences of low doses of ionizing radiations on differentiation and self-renewal capacities of human primary hematopoietic stem/progenitor cells (HSPC). We found that a single 20 mGy dose impairs the hematopoietic reconstitution potential of human HSPC but not their differentiation properties. In contrast to high irradiation doses, low doses of irradiation do not induce DNA double strand breaks in HSPC but, similar to high doses, induce a rapid and transient increase of reactive oxygen species (ROS) that promotes activation of the p38MAPK pathway. HSPC treatment with ROS scavengers or p38MAPK inhibitor prior exposure to 20 mGy irradiation abolishes the 20 mGy-induced defects indicating that ROS and p38MAPK pathways are transducers of low doses of radiation effects. Taken together, these results show that a 20 mGy dose of ionizing radiation reduces the reconstitution potential of HSPC suggesting an effect on the self-renewal potential of human hematopoietic stem cells and pinpointing ROS or the p38MAPK as therapeutic targets. Inhibition of ROS or the p38MAPK pathway protects human primary HSPC from low-dose irradiation toxicity.